Evaluation of imputation performance of multiple reference panels in a Pakistani population - Jiayi Xu; Dongjing Liu; Arsalan Hassan; Giulio Genovese; Alanna C. Cote; Brian Fennessy; Esther Cheng; Alexander W. Charney; James A. Knowles; Muhammad Ayub; Roseann E. Peterson; Tim B. Bigdeli; et al. (HGG Advances)
Summary: Genotype imputation is crucial for genome-wide association studies (GWASs), but reference panels and existing benchmarking studies prioritize European individuals. Consequently, it is unclear which publicly available reference panel should be used for Pakistani individuals, and whether ancestry composition or sample size of the panel matters more for imputation accuracy. Our study compared different reference panels to impute genotype data in 1,814 Pakistani individuals, finding the best performance balancing accuracy and coverage with meta-imputation with TOPMed and the expanded 1000 Genomes (ex1KG) reference. Imputation accuracy of ex1KG outperformed TOPMed for common variants despite its 30-fold smaller sample size, supporting efforts to create future panels with diverse populations.